Exploring bodily knowledge in Silek Tuo through the meaning of the Pencak silat movement as material for developing dance learning at the Universitas Negeri Jakarta - Romi Nursyam (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
Silat, apart from being a form of self-defence, is also a source of artistic inspiration for dance artists, including, in this case, Silek Tuo, which developed in Paninggahan, which is the “Parik Paga Nagari” (village protector). The purpose of the study was to find out and describe the meaning that existed in the Silek Tuo element, where the study included the conditions that must be fulfilled before the Silek Tuo practice, the meaning of the Silek Tuo itself from an Islamic perspective, and the meaning of the Silek Tuo movement, which would be applied in Pencak silat courses at the Dance Study Program at Jakarta State University. The method used in the research is the descriptive qualitative method, where the meaning of Silek Tuo is described in writing, with the method of collecting data using observation and interviews. The urgency of this research is to improve dance students' psychomotor affective and cognitive abilities about silat, especially the Silek Tuo. This study's results describe the conditions that must be met to learn Silek Tuo, the meaning of motion, and the correlation of Islamic law to Silek Tuo in Paninggahan